Peran Aparat Pengawas Intern Pemerintah (APIP) dalam Pengelolaan Keuangan Desa di Kabupaten Buton - La Ode Muhammad La Ode Muhammad; La Ode Syaiful Islamy; Rahmawati Rahmawati; Rininta Andriani (PROVIDER JURNAL ILMU PEMERINTAHAN, 2026)
Village financial management plays a crucial role in realizing transparent, accountable, and sustainable village development. However, various challenges persist, including the limited capacity of village officials, weak documentation, and the suboptimal implementation of cashless transactions. This study aims to analyze the role of the Government Internal Supervisory Apparatus (APIP) in village financial management in Buton Regency, focusing on the supervision mechanisms applied and the obstacles faced. The research employs a qualitative descriptive approach through in-depth interviews, participatory observation, and document analysis, using the Miles and Huberman interactive data analysis model. The results show that APIP plays a significant role through four stages of supervision: setting standards, reviewing results, comparing implementation with standards, and taking corrective actions. The Buton Regency Inspectorate has implemented supervision based on regulations and an early warning system, encouraging the follow-up of findings through educational approaches and technical assistance. Although this has positively impacted transparency and accountability, the implementation still faces obstacles such as limited human resources at the village level, low understanding of regulations, and minimal utilization of digital technology. In conclusion, the role of APIP in Buton Regency functions not only as an administrative controller but also as a coach and educator, serving as the key to achieving more accountable, transparent, and corruption-free village financial governance.